PENGARUH CAPITAL ADEQUACY RATIO DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSET PADA PT BANK MANDIRI - Eni Puji Astuti; Rahmi Hermawati; Rima Handayani (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA) at PT Bank Mandiri (Persero). This research is a type of quantitative research using descriptive analysis method and using data in financial reports in the form of balance sheets and income statements of PT Bank Mandiri (Persero). for ten years, namely the period 2011-2020. Based on the results of the study, it shows that partially the Capital Adequacy Ratio (CAR) has a significant negative effect on Return On Assets (ROA) and Loan to Deposit Ratio (LDR) has a significant positive effect on Return On Assets (ROA) at PT. Bank Mandiri (Persero). 2011-2020. Then simultaneously or together it shows that the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) have a significant effect on Return On Assets (ROA) and the magnitude of the influence of the independent variable on the dependent variable in this study is equal to 79.1% while the remaining 20.9% is influenced by other factors not examined in this study.